The Effects of Wind Regime and Sand Supply on the Coexistence of Barchans and Linear Dunes in China’s Qaidam Basin - Ma, Fang; Lü, Ping; Cao, Min (Frontiers in Earth Science, 2022)
Dunes composed of granular materials are present in deserts and other environments, such as subaqueous environments and environments on other planets, with very different time and length scales for their evolution. In arid regions, barchans (transverse dunes) develop under a unimodal wind regime, and are oriented perpendicular to the sand transport direction, whereas linear (longitudinal) dunes develop under a bimodal wind regime and are oriented parallel to the sand transport direction. However, field survey results cannot be explained solely by the wind because barchans and linear dunes can coexist under the same wind regime. Here, we investigated China’s Qaidam Basin, where barchans and linear dunes coexist. We measured dune morphology, analyzed wind data, and quantified the sand supply (equivalent sand thickness) to describe their development environment, and focused on the effect of sand supply to explore the combined effects of wind regime and sand supply on the coexistence of barchans and linear dunes. In our study area, barchans and linear dunes had low heights. The wind regime was narrowly bimodal, with low directional variability. The sand supply was limited (low equivalent sand thickness), but was greater for barchan chains than for barchans, and linear dunes had the smallest supply; the equivalent sand thickness in the linear dune areas was half that in barchan areas and one-quarter that in barchan chain areas. Except in the presence of topographical barriers and cohesive sediments, a unimodal or bimodal wind regime with an acute angle allows barchans and linear dunes to coexist under a low sand supply. The linear dunes and the barchans migrated along the resultant drift direction. Though we studied aeolian dunes, these findings will increase our understanding of these similar bedforms that develop in other planetary environments (e.g., Mars).